High-dose chemotherapy (HDCT) with auto-SCT in children with atypical teratoid/rhabdoid tumors (AT/RT): a report from the European Rhabdoid Registry (EU-RHAB) - Benesch, M.; Bartelheim, K.; Fleischhack, G.; Gruhn, B.; Schlegel, P. G.; Witt, O.; Stachel, Daniel; Hauch, H.; Urban, C.; Quehenberger, F.; Massimino, M.; Pietsch, T.; et al. (Bone Marrow Transplantation, 2014)
A retrospective analysis of data from the European Rhabdoid Registry (EU-RHAB) was performed to describe the outcome of children with atypical teratoid/rhabdoid tumors (AT/RT) who underwent high-dose chemotherapy (HDCT) with auto-SCT. Nineteen patients (male, n=15; median age at diagnosis 21 months) were identified. Nine patients presented with metastatic disease at diagnosis. A partial or subtotal resection was achieved in 11, a total resection in five and a biopsy in three patients. Patients received a median of six chemotherapy cycles prior to HDCT. Additional radiotherapy was performed in 14 patients (first-line, n=9; following progression, n=5). Six patients underwent tandem auto-SCT. Disease status before HDCT was CR in six, PR in eight, stable disease in two and progressive disease (PD) in two patients (data missing, n=1). With a median follow-up of 16 months, 14 patients progressed. Estimated progression-free and OS at 2 years were 29% (±11%) and 50% (±12%), respectively. At last follow-up, eight patients were alive (first CR, n=4; second CR, n=2; PR, n=1; PD, n=1). Eleven patients died of PD. Median time-to-progression was 14 months. Selected patients with AT/RT might benefit from HDCT with radiotherapy. The definitive impact of this treatment modality has to be evaluated prospectively in a randomized trial.
EVALuna2:18904